STRATEGI BERTAHAN HIDUP BURUH NELAYAN DI BAROMBONG KEC. TAMALATE KOTA MAKASSAR - Amir, Muhammad Fathuracman (UNIVERSITAS NEGERI MAKASSAR, 2018)
Strategy of Survive the Fishermen Laborers in Barombong Tamalate Sub-district, Makassar City. The purpose of this research is to determine the socio-economic condition of fishermen laborers and to know the income of fishermen laborers in met the needs of life reasonably and to know the Strategy of Survive the Fishermen Laborers in Barombong. This research is a type of survey research while based on the analysis approach including qualitative descriptive research with sample technique used is Random Sampling with a total sample is 149 respondents. There are three kinds of collecting data that used in this research, first Observation Techniques secondly Interview Techniques and thirdly Documentation Techniques. The results of this research are firstly Based on the socio-economic condition the level of education is still relatively low only finished primary school. Secondly the income level of fishermen laborers has a moderate income level which has 80.54 percent, based on UMP of South Sulawesi Province the income level of fishermen laborers has not met the needs of life reasonably. Thirdly The strategies employed by fishermen laborers in survival include adding working days, sending household members to work, and minimizing expenses, getting used to living frugally, and utilizing government programs.